2022
DOI: 10.3390/plants11070902
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodistillation and Microwave Extraction of Volatile Compounds: Comparing Data for Twenty-One Veronica Species from Different Habitats

Abstract: Free volatile compounds were isolated from 21 Croatian Veronica species studied by hydrodistillation (HD) and microwave extraction (ME) and analyzed by gas chromatography coupled with mass spectrometry. Principal Component Analysis (PCA) distinguished some clusters based on the relative proportion of major compounds, such as hexadecanoic acid, hexahydrofarnesyl acetone, phytol, E-caryophyllene, and caryophyllene oxide, which were identified in all species studied by both isolation methods. In addition to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…In the composition of the EO extract of V. anagalloides, the dominant compounds are hexahydrofarnesyl acetone (16.17%) and β-ionone (13.13%). Comparing the composition of the oil components of this species with the data previously published in the article by Dunkić et al [2], we note a similarity in the concentration value of hexahydrofarnesyl acetone. In that research, the composition of oil components obtained by classical (Clevenger apparatus, HD) and modern hydrodistillation (MAE) was compared, so the value of hexahydrofarnesyl acetone in the EO of V. anagalloides was 14.33% for HD and 19.12% for MAE [2].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the composition of the EO extract of V. anagalloides, the dominant compounds are hexahydrofarnesyl acetone (16.17%) and β-ionone (13.13%). Comparing the composition of the oil components of this species with the data previously published in the article by Dunkić et al [2], we note a similarity in the concentration value of hexahydrofarnesyl acetone. In that research, the composition of oil components obtained by classical (Clevenger apparatus, HD) and modern hydrodistillation (MAE) was compared, so the value of hexahydrofarnesyl acetone in the EO of V. anagalloides was 14.33% for HD and 19.12% for MAE [2].…”
Section: Discussionsupporting
confidence: 80%
“…Comparing the composition of the oil components of this species with the data previously published in the article by Dunkić et al [2], we note a similarity in the concentration value of hexahydrofarnesyl acetone. In that research, the composition of oil components obtained by classical (Clevenger apparatus, HD) and modern hydrodistillation (MAE) was compared, so the value of hexahydrofarnesyl acetone in the EO of V. anagalloides was 14.33% for HD and 19.12% for MAE [2]. Moreover, in Nazlić et al article [7], a much lower β-ionone relative percentage was found in this sample obtained by MAE compared to this study: only 4.22%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For this reason, a systematic study of the specialized metabolites that make up the free volatile compounds (FVCs) is being conducted. Dunkić et al [6] investigated the composition of FVCs of the 21 Croatian Veronica species contained in the lipophilic layer of extracts obtained by classical (hydrodistillation, HD) and green (microwave-assisted, MAE) extraction [6]. These extraction methods yield the two layers mentioned earlier, the lipophilic layer (LL) or essential oil (EO) and the aqueous layer (hydrosols).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, another important part of this research is focused on the comparison of the composition of FVCs from the hydrosols and the lipophilic layer obtained by both extraction methods. The compositions of the LL of all 10 Veronica species studied that will be used for comparison were published in our previous work [6].…”
Section: Introductionmentioning
confidence: 99%